Simulation of neutron influence on tungsten mirrors - Voitsenya, V. S.; Alimov, A. K.; Balden, M.; Bardamid, A. F.; Belyaeva, A. I.; Galuza, A. A.; Kasilov, A. A.; Kolenov, I. V.; Konovalov, V. G.; Ryzhkov, I. V.; Savchenko, A. A.; Shtan, A. F.; et al. (National Science Center "Kharkiv Institute of Physics and Technology", 2013)
The effect of neutron irradiation on behavior of optical characteristics for two types of tungsten mirrors was modeled. Preliminary irradiated rcW and WJ-IG mirrors with 20 MeV W6+ ions were used for experiments. Changes in the surface morphology and optical characteristics of the samples were investigated in the sputtering process.

Вивчався вплив нейтронного опромінення на поведінку оптичних властивостей двох типів вольфрамових дзеркал rcW та WJ-IG. Дзеркала попередньо були опромінені іонами W6+ з енергією 20 МеВ. Під час процесу розпилення досліджувалися зміни морфології поверхні та оптичних властивостей зразків.
Модельні дослідження властивостей вольфрамових дзеркал при нейтронному опроміненні
Keywords: neutron irradiation; tungsten mirrors; rcW mirrors; surface morphology; нейтронне опромінення; оптичні властивості; вольфрамові дзеркала; WJ-IG mirrors